Oral cancer cell to endothelial cell communication via exosomal miR-21/RMND5A pathway - Yu-qi Sun; Bing Wang; Lin-wei Zheng; Ji-hong Zhao; Jian-gang Ren (BMC, 2024)
Abstract Required for meiotic nuclear division 5 homolog A (RMND5A), a novel ubiquitin E3 Ligase, has been reported to correlate with poor prognosis of several cancers. However, its role in endothelial cells has not been reported. In this study, overexpression of RMND5A in human umbilical vein endothelial cells (HUVECs) was performed via lentiviral infection, followed by MTT, would healing and tube formation assay as well as signaling analysis. Moreover, crosstalk between HUVECs and oral squamous cell carcinoma (OSCC) cells was investigated by indirect co-culture with condition medium or tumor cell derived exosomes. Our results showed that overexpression of RMND5A reduced the proliferation, migration and tube formation ability of HUVECs by inhibiting the activation of ERK and NF-κB pathway. Interestingly, OSCC cells can inhibit RMND5A expression of endothelial cells via exosomal miR-21. In summary, our present study unveils that OSCC cells can activate endothelial cells via exosomal miR-21/RMND5A pathway to promote angiogenesis, which may provide novel therapeutic targets for the treatment of OSCC.